Reading Instruction for English Learners With Learning Disabilities: What Do We Already Know, and What Do We Still Need to Learn?. Issue 166 (26th June 2019) - Hall, Colby; Steinle, Paul K.; Vaughn, Sharon
Abstract: This paper reviews findings from four research syntheses that report the effects of academic language and/or reading interventions on language and reading outcomes for English learners who have or are at risk for learning difficulties. Studies included in the syntheses varied in research design and addressed multiple areas of reading and language. There was disagreement between syntheses as to the extent of research evidence in favor of particular instructional practices. For ELs with learning difficulties in kindergarten and first grade, however, there was strong consensus that multiple‐component reading instruction that includes phonological awareness and phonics instruction is associated with improved word reading outcomes. It may also be beneficial to provide oral language, vocabulary, and reading comprehension instruction; nevertheless, there is a need for future research on instructional interventions that aim to improve reading comprehension outcomes for this population.